King Midas and the Gold - Frith, Alex; Illustrated by Simona Sanfilippo and Reading Consultant Allison Kelly (London Usborne, 2008)
King Midas loves gold, but his greed soon gets him into trouble. This lively retelling of a classic Greek myth has easy to read text and fun puzzles to try after the story.
Include Color Illustrations
Keywords: Midas (Legendary character) -- Mythology, Greek -- Children's stories